The general equation of a line is given by:
![\begin{gathered} y=mx+c \\ \text{where m = slope} \\ c=\text{intercept} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g3vd7qvret5xjnj18kwv0qvm0ruqixpepr.png)
Given the line 2x -4y = -3
Step 1: Re-write the equation by making y the subject
![\begin{gathered} 4y=2x+3 \\ y=(2)/(4)x+(3)/(4) \\ y=(1)/(2)x+(3)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/me6pf14eurvs2ef3d8i7n0gdulty2ieeqy.png)
Since we have the equation of the line to be
![y=(1)/(2)x+(3)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/lf32vhfcz3p65kwv7tzgo6cjd4ti6pnj40.png)
Step 2: Obtain the slope of this line
![\text{slope}=m=(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/htkti6us5ksqn11sqqdife28gzqspi3r5v.png)
Step 3: Obtain the slope perpendicular to this line.
If two line are perpendicular, then
![m_1m_2=-1](https://img.qammunity.org/2023/formulas/mathematics/college/g06uuiirl5abnt1q62hvbbgwyhsoapoxn1.png)
so that
![m_2=-(1)/(m_1)](https://img.qammunity.org/2023/formulas/mathematics/college/famfci9sb6car80iseo3b973mc71ztg8tq.png)
![m_2=-(1)/((1)/(2))=-2](https://img.qammunity.org/2023/formulas/mathematics/college/uwr04q8okwbuy2xctf332k29m86md2u70s.png)
Hence the slope of the new line will be = -2
Step 4: Obtain the equation of the line using the formula:
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
where
![\begin{gathered} x_1=3,y_1=4,and\text{ } \\ m=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k39yemw7k9iu3udbjqsc7eqg2nlgz5uuty.png)
Thus,
![y-4=-2(x-3)](https://img.qammunity.org/2023/formulas/mathematics/college/4omnvg3dcuy4ug4hcxea2val0vjk25e22k.png)
=>
![\begin{gathered} y-4=-2x+6 \\ y=-2x+6+4 \\ y=-2x+10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kaqt462tioyiuohhbb9m0vmfmb16d6sxlw.png)
The equation of the line that s perpendicular to the line is
=> y= -2x +10
This can also be written in the form ax+by=c
as
Making the constant to be on the right-hand side and the variables to be on the left and side as shown below
Hence,
2x+y=10